Interleukin 10 (IL-10) and transforming growth factor beta (TGF- ß) expression in intestinal mucosa of alpaca crias (Vicugna pacos) - Burga C., Cesar (2017)
The aim of the present study was to evaluate the relative expression levels of cytokines IL-10 and TGF-β in the intestinal mucosa of clinically healthy alpacas from 2 to 47 days old. The animals were classified in three age groups (six animals per group): 2-8 days old (group 1), 10-21days old (group 2) and 26-47-days old (group 3), regardless sex or breed. The midportion of jejunum of each animal was collected; total RNA was extracted and then analyzed by real-time RT-PCR technique using IL-10 and TGF-β specific primers. The relative mRNA expression analysis was done using the comparative 2-ΔΔCt method. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was used as housekeeping gene and jejunum of three 11-month-old fetuses were used as calibrators. The results showed that IL-10 mRNA expression levels were 7.21±1.02 (group 1), 13.53±1.26 (group 2), and 18.77±1.48 (group 3) times as expressed by the calibrate group with significant difference between age groups (p<0.05). Also, TGF-β mRNA expression levels were 2.18±0.23 (group 1), 3.03±0.18 (group 2), and 4.06±0.15 (group 3) times as expressed by the calibrate group with significant difference between age groups (p<0.05). The expression of IL-10 and TGF-β mRNA was age dependent, increasing significantly in older animals.